Energy Efficiency Performances of LVDC Nanogrids Powered Buildings - Anis Ammous; Ammar Assaidi; Abdulrahman Al Ahdal; Kaiçar Ammous (Journal of Engineering)
The Low Voltage Direct Current (LVDC) system concept has been growing in the recent times due to its characteristics and advantages like renewable energy source compatibility, more straightforward integration with storage utilities through power electronic converters, and distributed loads. This paper presents the energy efficiency performances of a proposed LVDC supply concept and other classical PV chains architectures. A PV source was considered in the studied nanogrids. The notion of relative saved energy (RSE) was introduced to compare the studied PV systems energy performances. The obtained results revealed that the use of the proposed LVDC chain supply concept increases the nanogrid efficiency. The installed PV power source in the building should be well sized regarding the consumed power in order to register a high system RSE. The efficiency of the new LVDC architecture is 10% higher than the conventional LVDC one.